The Influence of Transformational Leadership Style, Work Motivation and Organizational Culture on the Teachers and Non-Educators' Performance (Case Study of the Tanbihul Ghofilin Education Foundation, Surabaya) - Sari, Alda Ayu (Program Pascasarjana STIE Amkop Makassar, 2023)
This study aims to determine the effect of transformational leadership style, work motivation, organizational culture on teacher performance and non- education personnel. This research is expected to improve the performance of Teachers & Non-Education Personnel of the Tanbihul Ghofilin Surabaya Education and Da'wah Foundation. The research used is quantitative research. The data collection technique in this study used a purposive sampling method with a questionnaire. Respondents of this study were Teachers & Non-Education Personnel of the Tanbihul Ghofilin Surabaya Education and Da'wah Foundation. The population of this study were 50 people and the sample taken was 47 people. The data analysis technique used multiple linear regression with the help of IBM SPSS statistic 26.0. The results of this study indicate that the first and second hypotheses are rejected, while the third hypothesis is accepted. Organizational culture has a significant effect on improving the performance of Teachers & Non- Education Personnel, while Transformational Leadership Style and Work Motivation have no and insignificant effect on improving the performance of Teachers & Non-Education Personnel. This is because employees are dominated by female teachers who are over 20 years old, usually they are more oriented to how much wages are earned in increasing their level of performance. And employees feel that the work they are doing is a responsibility that they really have to do even without the work motivation they get. So that with the results of this research, the Tanbihul Ghofilin Education and Da'wah Foundation needs to pay attention to these two variables in order to achieve maximum performance for better company results as well.